HeinOnline An Online Archive of Law Journals / Richard J. Marisa. - Marisa, Richard J. (Distributed by ERIC Clearinghouse, 2001)
Law is grounded in the past, in the decisions and reasoning of generations of lawyers, judges, juries, and professors. Ready access to this history is vital to solid legal research, and yet, until 2000, much of it was buried in vast collections of aging paper journals. HeinOnline is a new online archive of law journals. Development of HeinOnline began in late 1997 through the cooperation of Cornell Information Technologies, William S. Hein & Co., Inc. of Buffalo, New York, and the Cornell Law Library. Built upon the familiar Dienst and new Open Archive Initiative protocols, HeinOnline extends the reliable and well-established management practices of open access archives like NCSTRL and CoRR to a subscription-based collection. The decisions made in creating HeinOnline, Dienst architectural extensions, and issues that have arisen during operation of HeinOnline are described in this paper. The paper discusses Dienst, a framework for implementing digital library systems; the HeinOnline design; creating a working library; production experience; and future plans. (Author/AEF)